Gains and Pains from Contract Research: A Transaction and Firm-level Perspective - Ulrich Kaiser; Christoph Grimpe (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Determining the research and development (R&D) boundaries of the firm as the choice between internal, collaborative and external technology acquisition has since long been a major challenge for firms to secure a continuous stream of innovative products or processes. While research on R&D cooperation or strategic alliances is abundant, little is known about the outsourcing of R&D activities to contract research organizations and its implications for innovation performance. This paper investigates the driving forces of external technology sourcing through contract research based on arguments from transaction cost theory and the resource-based view of the firm. Using a large and comprehensive data set of innovating firms from Germany our findings suggest that technological uncertainty, contractual experience and openness to external knowledge sources motivate the choice for engaging in contract research activities. Moreover, we show that internal and external R&D sourcing are complements: the marginal contribution of internal (external) R&D is the larger the more firms spend on external (internal) R&D.
Keywords: O32; C24; 330; Contract research; innovation; transaction cost theory; firm capabilities; Innovation; Industrielle Forschung; Outsourcing; Forschungskooperation; Transaktionskosten; Ressourcenorientierter Ansatz; Deutschland; Auftragsforschung